2016
DOI: 10.1097/inf.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Pediatric Invasive Meningococcal Disease in Spain (2008–2013)

Abstract: Serogroup B invasive meningococcal infection explains substantial morbidity and mortality in Spain, occurring mainly in infants. The recent availability of a vaccine against serogroup B may change this scenario. Given that the vast majority of the cases occur in otherwise healthy children, inclusion of the meningococcal B vaccine in the national immunization program should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
4
17
3
Order By: Relevance
“…During the study, 21 patients died, giving us a total CFR of 7%. This number was at the same level as the CFR seen in other similar studies of children . The serogroup C isolates showed a nonsignificant higher CFR of 15%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…During the study, 21 patients died, giving us a total CFR of 7%. This number was at the same level as the CFR seen in other similar studies of children . The serogroup C isolates showed a nonsignificant higher CFR of 15%.…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of sequelae in our study was 3%, but only severe, permanent sequelae were registered. This was lower than the percentage registered in many other studies, where the incidence of sequelae was reported to be 8–19% . One explanation for this difference could, of course, be differences in the registration criteria, with variations between suspected, smaller and severe sequelae.…”
Section: Discussioncontrasting
confidence: 67%
“…Streptococcus pyogenes -5,4 to 7, 7%, Streptococcus pneumoniae and Haemophilus influenzae both around 4% [19][20][21][22][23]. On the other hand, the prevalence of purulent meningitis in infections caused by Neisseria meningitidis is substantially higher, between 40 and 65%, depending on individual serotypes and regional differences [24][25][26][27][28]. Reasons for lower mortality rates in patients with purulent meningitis (in comparison with sepsis) caused by Capnocytophaga spp.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed differences form studies in the United States were S. aureus, Pseudomonas species and Enterobacteriacae (mainly E.coli) were the main pathogens isolated. [19] Vaccinations are an essential tool in our fight against infectious disease [4,20,21], and they have greatly reduced the global burden of infectious disease [21]. Although most patients were up-to-date according to their local immunisation schedule, we found that there was a considerable burden of mortality and morbidity caused by vaccine preventable infections, particularly meningococcal and pneumococcal disease.…”
Section: Mortality Was Highest In Children With Sepsis As Defined By mentioning
confidence: 90%